ANALISIS PERAN ORANG TUA DAN GURU DALAM KEMANDIRIAN ANAK - Okta Bela, Wulan; Awalia, Eby Sania; Melinda, Meta; Ananta, Selvia; Anjani, Adelia Putri (HYPOTHESIS : Multidisciplinary Journal Of Social Sciences, 2023)
The aim of this research is to describe the role of parents and teachers in children's independence. The research method used in this research uses a qualitative research or case study type research approach. Interviews with five parents and five teachers were used as a data collection technique. Based on the results of interviews with parents, parents teach their children independence at the age of 3-5 years. Meanwhile, people's efforts to develop independence begin with teaching them to wash their hands before handling food, teaching them small things such as eating, teaching them how to drink, and preparing school books. Parents also emphasize the importance of the family environment in influencing children's growth and development. Teachers' efforts to develop students' independence consist of giving students independent assignments, providing motivation, and providing fun material. The strategies used by teachers are to increase children's independence by making them curious about new information and finding out for themselves, providing opportunities for students so that students can learn and be independent by providing fun material, making a list of activities and praising and recognizing when students do something well. In addition, teachers emphasize the relationship between independence and emotional intelligence, stating that emotional intelligence plays an important role in students' commitment to tasks and achieving maximum learning.